Biomarkers of physiological responses of Octopus vulgaris to different coastal environments in the western Mediterranean Sea. (March 2018) - Sillero-Ríos, J.; Sureda, A.; Capó, X.; Oliver-Codorniú, M.; Arechavala-Lopez, P.
Abstract: The increase of pollutants in coastal seawater could produce several harmful biological effects on marine organisms related to the production of reactive oxygen species (ROS) causing cellular and tissue damages through oxidative stress mechanisms. Common octopuses ( Octopus vulgaris ) inhabiting coastal areas under high anthropogenic activity of Mallorca (W-Mediterranean Sea) have the ability to control oxidative damage by triggering antioxidant enzyme responses. Analyzing the digestive glands, octopuses from human-altered coastal areas showed higher activity of superoxide dismutase (SOD), catalase (CAT) and glutathione S-transferase (GST) compared to octopuses from non-influenced coastal waters (i.e. marine reserve area). Higher metallothionein (MT) concentrations and lack of malondialdehyde (MDA) variations also reflect adaptations of O . vulgaris to polluted areas. This is the first study assessing the levels of the oxidative stress biomarkers on O . vulgaris in the Mediterranean Sea, revealing their usefulness to assess diverse environmental pollution effects on this relevant ecological and commercial species. Graphical abstract: Unlabelled Image Highlights: Common octopus increases antioxidants enzymes activity to cope with oxidative stress. Variations in MT concentrations show a detoxification strategy of common octopus. A lack of MDA variations may reflect an adaptation of O . vulgaris to polluted areas. Physiological responses of O . vulgaris are useful biomarkers of human-altered areas.